Immunosuppressive adenosine-targeted biomaterials for emerging cancer immunotherapy - Wei, Qi; Zhang, Lening; Zhao, Nan; Cheng, Zhihua; Xin, Hua; Ding, Jianxun (Frontiers in Immunology, 2022)
Immunotherapy has paved the way for the future of cancer therapy but still faces significant challenges, such as the occurrence of immune escape or suppression. In this regard, adenosine modulates the immune responses of immune cells and maintains immune tolerance. Emerging adenosine pathway inhibitors are considered a breakthrough in cancer immunotherapy. Among them, the top-down blockade of adenosine signaling axis is emphasized. Then, the adenosine pathway blockade-based combination therapy is focused on. However, these therapeutic strategies rely on adenosine inhibitors, mainly small molecules or proteins, still limited by non-specific effects and off-target toxicity. Therefore, the synergistic nanomedicine with accurate delivery targeting deeper tumors is focused on in preclinical studies. This review discusses how adenosine reshapes the immunosuppressive microenvironments through its effects on immune cells, including lymphocytes and myeloid cells. Additionally, it will be the first discussion of a comprehensive strategy of biomaterials in modulating the adenosine signaling pathway, including inhibition of adenosine production, inhibition of adenosine binding to immune cells, and depletion of adenosine in the microenvironments. Furthermore, biomaterials integrating multiple therapeutic modalities with adenosine blocking are also discussed, which is promising for promoting cancer immunotherapy.